PENYULUHAN MENGENAI PENCEGAHAN DAN PENGOBATAN MALARIA DI DESA CAMPLONG, KABUPATEN KUPANG, NTT - Lidia, Kartini; Setianingrum, Elisabeth Levina Sari; Riwu, Magdarita; Lada, Christina Olly; Pasa, Irene Rosario Mala; Pakaenoni, Agnes Tiara Maharani D.; Stevanovic, Claudio; Suryanta, Andrie; Wibawa, Krisanty Lintang (Jurnal Media Tropika, 2023)
Malaria is one of the parasitic infectious diseases that is still a world health problem, especially in tropical countries including Indonesia. Malaria is still one of the causes of death in both adults and children. According to the World Health Organization (WHO) malaria report in 2020, the estimated number of malaria cases in the world in 2019 reached 229 million cases in 87 malaria-endemic countries, down from 238 million in 2000. Data from the Indonesian Ministry of Health regarding the achievement of Malaria Elimination Districts / Cities shows that Indonesia's Annual Paracite Incidence (API) rate in 2020 reached 0.87. Data from the 2021 NTT Malaria Report from the NTT Provincial Health Office shows that in 2021, the number of positive malaria cases in NTT Province was 9,419 cases with an API of 1.72 per 1000 population and 10 cases of death due to malaria. In addition, in 2021 there are 14 districts/cities in NTT classified as low endemic areas, and there are still 3 districts/cities classified as high endemic areas with the dominant species being plasmodium falciparum. Kupang Regency is one of the areas targeted for malaria elimination in 2020. Camplong Village, Fatuleu District, is included in Kupang Regency which is the target of elimination in 2022. Aims and objectives: Increase awareness of the people of Camplong village on the dangers of malaria, malaria prevention and treatment so that the 2030 NTT malaria elimination target can be achieved. Method of implementation of activities: Counseling and treatment Output indicators produced: The implementation of counseling for the community in the Camplong Village area of Hamlet 2 totaling 88 residents consisting of 45 women and 43 men. Conclusion: The activities of malaria counseling and treatment services in Camplong village 2 hamlet 2 RT 5,6,7 are one of the programs that can provide benefits to the community, namely increasing knowledge about malaria, how to prevent and treat malaria. This is very important to improve the health of the Camplong community while helping the malaria elimination program carried out by the government. Similar activities must continue to be carried out and in collaboration with local Puskesmas so that the target of malaria elimination in 2030 for Kupang district in particular and Indonesia in general can be achieved.